Profiling and analysis of starch synthase at different trunk heights of sago palm (metroxylon sagu rottb.) - George, Deng Anyie (Universiti Malaysia Sarawak (UNIMAS), 2012)
Research on sago palm has been a main focus in Sarawak state as it has a great potential to boost the economy. Various studies have been performed on this starchy plant and one of it is the study on its starch biosynthesis pathway. Starch synthase was identified as one of the enzymes that play vital role in biosynthesis of starch. Therefore the profiling and characterization of starch synthase has been studie . Three palms were sampled from Bau district, specifically from KampungTanjong and KampungSidoh. Targeted part for studies on the palm wasthe base height, middle height, and top height of the trunk. Initial studies were the optimization of specific extraction protocol for starch synthase from sago palm withthe GBSS buffer was identified as the most suitable buffer. The best method for post extraction purification and concentration was determined as the cold acetone precipitation method. Then total starch content in 1 g/mL of sample and total protein concentration was measured and undergoes ANOV A, with the statistical analysis showed no significant difference (p < 0.05) oftotal starch content in 1 g/mL of sample and total protein concentration among each palms. However ANOVA on the data for starch content between the inner part and outer part of the trunk showed the outer part contained more starch than the inner part. Presence of Starch Synthase (SS) in optimization-treated sample and all samples were confirmed through HPLC analysis as quantitative result and SDS-P AGE analysis as qualitative result. Subsequently the activities of SS were assayed through spectrophotometer. The results showed no significant different (p < 0.05)between SS activity with the trunk's height. Developments of specific primers have been done by few researchers on sago palm. In this study, a pairs of PCR primers were designed from cDNA library of sago palm and others starchy plants. The studies were initiated by total RNA isolation and RNA's conversion to cDNA. The cDNAintegrity was confirmed using polymerase chain reaction technique using in house gene primer, called elf-F and elf-R. The cDNA was further amplified and sequenced. Primer with labeled ssJ was confirmed to be a specific primer for starch synthase as the BLAST resulted in percentage of similarities with Zea mays full length cDNA clone (79%), Zea mays starch synthase IIc precursor (68%), Triticumaestivllm starch synthase IIc precursor (77%), and Oryza Sativa soluble starch synthase II-I mRNA 77%).Characterization of SS in sago palm's trunk were further analyzed through Western blotting and the results has confirmed the presence of SS isoform at the size of 66.2 kDa, 45 kDa, 29 kDa, 26 kDa, and 17.7 kDa molecular mass.Although Northern blot analysis was failed, the specificity of the designed ssFI and ssRI primer was confirmed. Conclusively, this research has successfully identified the presence and size of SS isoform in sago palm's trunk and its activity was observed to be slightly gradually increased with the trunk's height.